Quantum mechanical/molecular mechanical analysis of the catalytic mechanism of phosphoserine phosphatase - Krachtus, Dieter; Smith, Jeremy C.; Imhof, Petra (Molecules, 2018)
Phosphoserine phosphatase (PSP), a member of the haloacid dehalogenase (HAD) superfamily that comprises the vast majority of phosphotransferases, is likely a steady-state regulator of the level of d-serine in the brain. The proposed catalytic cycle of PSP consists of a two-step mechanism: formation of a phospho-enzyme intermediate by phosphate transfer to Asp11 and its subsequent hydrolysis. Our combined quantum mechanical/molecular mechanical (QM/MM) calculations of the reaction pathways favour a dissociative mechanism of nucleophilic substitution via a trigonal-planar metaphosphate-like configuration for both steps, associated with proton transfer to the leaving group or from the nucleophile. This proton transfer is facilitated by active site residue Asp13 that acts as both a general base and a general acid. Free energy calculation on the reaction pathways further support the structural role of the enzymatic environment and the active site architecture. The choice of a proper reaction coordinate along which to bias the free energy calculations can be guided by a projection of the canonical reaction coordinate obtained from a chain-of-state optimisation onto important internal coordinates.
Gesehen am 28.10.2019